Delayed microhyphaema with intraocular lenses: a retrospective study of eight patients. Issue 2 (February 1989) - Butler, L; Roper-Hall, M J
Abstract : Eight patients with delayed microhyphaema were identified from a computer data base of 1209 patients who had had cataract extraction with Binkhorst 4-loop intraocular lens insertion. Five cases were recurrent. The cases were examined to try and identify an underlying cause. No single cause was identified, but trauma, hypertension, and oral anticoagulants were found to be associated. Some episodes were asymptomatic. The wide variety of surgical technique and style of lens with which this complication has been reported implies multiple causative factors. The source of the bleeding and its management are discussed.